The Effects of Solid State Fermentation on Nutrient Composition of Olive Cake with Aspergillus Niger and Bacillus Subtilis - Ataei, AH; Kirkpinar, F (Journal of the Hellenic Veterinary Medical Society, 2025)
Olive cake is a cost-effective feed ingredient with potential in animal nutrition; however, its application is limited due to low protein content, high fiber levels, and anti-nutritional factors. This study aimed to enhance the nutritional value of olive cake through solid-state fermentation using Aspergillus niger and Bacillus subtilis. Aspergillus niger and Bacillus subtilis were applied to the olive cake, and samples were incubated at 30°C for 24, 48, and 72 hours. Samples were divided into control and treatment groups, each containing 200 g of olive cake mixed with 100 ml of distilled water. The results showed that solid-state fermentation generally increased crude protein content and decreased crude fiber content (P<0.05). A significant increase in crude protein content was observed only with Bacillus subtilis, while a significant decrease in crude fiber content was noted only with Aspergillus niger (P<0.05). Neutral detergent fiber content remained unchanged across all groups (P>0.05). Although acid detergent fiber and acid detergent lignin contents generally decreased in all fermented groups, this reduction was statistically significant only in the groups treated with Aspergillus niger (P<0.05). Moreover, a significant decrease in nitrogen-free extract, metabolizable energy, sugar, total phenolic content, total flavonoid content, and antioxidant activity was observed in all fermented olive cake groups (P<0.05). The findings suggest that olive cake, an inexpensive and underutilized by-product, can be effectively transformed into a valuable feed ingredient and/or feed additive for animal nutrition through solid-state fermentation.